The diagnostic accuracy of CT-guided percutaneous core needle biopsy and fine needle aspiration in pulmonary lesions: a meta-analysis. Issue 1 (January 2016) - Zhang, H.-F.; Zeng, X.-T.; Xing, F.; Fan, N.; Liao, M.-Y.
Abstract : Aim: To determine and compare the diagnostic value of computed tomography (CT)-guided percutaneous core needle biopsy (PCNB) and percutaneous fine-needle aspiration biopsy (PNAB) in pulmonary lesions. Materials and methods: PubMed, EMBASE, and the Web of Science were systematically searched for relevant studies that investigated the diagnostic accuracy of CT-guided PCNB and/or PNAB for pulmonary lesions up to December 2014. After study selection, data extraction, and quality assessment, the sensitivity (SEN), specificity (SPE), diagnostic odds rate (DOR), positive likelihood ratios (PLR), negative likelihood ratios (NLR), and summary receiver operating characteristic (SROC) curves were calculated using the Meta-Disc 1.4 software. Results: Nineteen publications, including 21 independent studies, met the inclusion criteria. Of them, 15 studies were included in the PCNB group and six studies in the PNAB group. The pooled SEN, SPE, DOR, PLR, NLR, and SROC were 0.95, 0.99, 54.72, 0.06, 821.90, and 0.98 in the PCNB group and 0.90, 0.99, 24.71, 0.14, 210.72, and 0.98 in the PNAB group, respectively. Conclusion: Based on current evidence, both PCNB and PNAB can be used as diagnostic methods to distinguish benign and malignant pulmonary lesions; the difference between PCNB and PNAB regarding diagnostic accuracy of benign or malignant pulmonary lesions is not obvious. Highlights: We systematically searched the databases of PubMed, Embase, Web of Science for studies published in English in the field of diagnostic accuracy of CT-guided PCNB or PNAB for pulmonary lesions. Nineteen researches including 21 studies were included in our analysis, with 15 in the group of PCNB and 6 in the group of PNAB. We compared the pooled sensitivity (SEN), specificity (SPE), diagnostic odds rate (DOR), positive likelihood ratios (PLR), negative likelihood ratios (NLR) and summary receiver operating characteristic (SROC) curves in these two methods. Based on our current evidence, both PCNB and PNAB can be used as major diagnostic methods to distinguish benign pulmonary lesions and malignant ones. However, the difference between them is not obvious.